Activation of CD137 Signaling Enhances Vascular Calcification through c-Jun N-Terminal Kinase-Dependent Disruption of Autophagic Flux. (26th September 2018) - Chen, Rui; Xu, Yao; Zhong, Wei; Li, Bo; Yang, Ping; Wang, Zhong Qun; Shao, Chen; Wang, Cui Ping; Yan, Jin Chuan
Abstract : Background. Vascular calcification is widespread and clinically significant, contributing to substantial morbidity and mortality. Calcifying vascular cells are partly derived from local vascular smooth muscle cells (VSMCs), which can undergo chondrogenic or osteogenic differentiation under inflammatory environment. Recently, we have found activation of CD137 signaling accelerated vascular calcification. However, the underlying mechanism remains unknown. This study aims to identify key mediators involved in CD137 signaling-induced vascular calcification in vivo and in vitro. Methods. Autophagy flux was measured through mRFP-GFP-LC3 adenovirus and transmission electron microscopy. Von Kossa assay and alkaline phosphatase (ALP) activity were used to observe calcification in vivo and in vitro, respectively. Autophagosome-containing vesicles were collected and identified by flow cytometry and Western blot. Autophagy or calcification-associated targets were measured by Western blot, quantitative real-time PCR, and immunohistochemistry. Results. Treatment with the agonist-CD137 displayed c-Jun N-terminal kinase- (JNK-) dependent increase in the expression of various markers of autophagy and the number of autophagosomes relative to the control group. Autophagy flux experiments suggested that agonist-CD137 blocked the fusion of autophagosomes with lysosomes in cultured VSMCs. Calcium deposition, ALP activity, and the expression of calcification-associated proteins also increased in agonist-CD137 group compared with anti-CD137 group, which could be recovered by autophagy stimulator rapamycin. Autophagosome-containing vesicles collected from agonist-CD137 VSMCs supernatant promoted VSMC calcification. Conclusion. The present study identified a new pathway in which CD137 promotes VSMC calcification through the activation of JNK signaling, subsequently leading to the disruption of autophagic flux, which is responsible for CD137-induced acceleration of vascular calcification.